Megalopolitan Manila: Striving Towards a Humane and World Class Megacity - Ruben G. Mercado (Philippine Institute for Development Studies (PIDS), 1998)
A world-class metropolis connotes a metropolitan settlement where infrastructure and services are considered at par with world standards in terms of sophistication, efficiency and quality of services. Admittedly, Metro Manila still has much to hurdle in relation to the provision of good transportation and making accessible the basic utilities like water, power and communication facilities. This paper highlights the issues and problems confronting Metro Manila by evaluating transport and traffic management, solid waste management, land use planning and infrastructure development.
Keywords: 330; urbanization; service delivery